2020
DOI: 10.3390/math8020224
|View full text |Cite
|
Sign up to set email alerts
|

New Framework for Quality Function Deployment Using Linguistic Z-Numbers

Abstract: Quality function deployment (QFD) is a useful design quality control tool in service enterprises and manufacturing enterprises. However, there are several issues in extant QFD frameworks, that is, in three aspects: description of evaluation information, weight determination of expert team members (TMs), and weight identification of customer requirements (CRs). In order to address these issues, a novel QFD framework is first proposed utilizing linguistic Z-numbers (LZNs) with integrated subjective and objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 54 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Several studies have shown that information is not completely reliable in many MCDM processes [10][11][12]. Especially in the problem with complex information source and subjective evaluation information, a large amount of incomplete reliable information exists [13]. Z-number is a new concept integrating both cognitive information and the reliability of information, produced by Zadeh in 2011 [14].…”
Section: Methods For Npp Site Selectionmentioning
confidence: 99%
“…Several studies have shown that information is not completely reliable in many MCDM processes [10][11][12]. Especially in the problem with complex information source and subjective evaluation information, a large amount of incomplete reliable information exists [13]. Z-number is a new concept integrating both cognitive information and the reliability of information, produced by Zadeh in 2011 [14].…”
Section: Methods For Npp Site Selectionmentioning
confidence: 99%
“…In order to address this problem, Zadeh [21] proposed the Z-number to describe the reliability of information, and it can better capture the expression nature of experts. Owing to its superiority and availability, the Z-number has been widely used in logistics service provider selection [22], economy development program selection [23], hospital performance management [24], and so on, but its application in supplier selection is not common yet. In this work, the Z-number is introduced to handle the uncertainty of decision-making, in order to determine the optimal nuclear power equipment supplier.…”
Section: Supplier Selection Methodsmentioning
confidence: 99%
“…Casanovas-Rubio et al [27] developed a method for assessing the sustainability of trenches based on the MIVES decision-making method. Chao Song et al [28] explore the structure of Quality Function Deployment (QFD) using linguistic Z-numbers (LZNs) and integrate the weights of expert team members and customer needs. Here, Step Wise Weight Assessment Ratio Analysis (SWARA) and Standard Deviation (SD) methods are presented to get the subjective and objective weights of customer needs.…”
Section: Literature Reviewmentioning
confidence: 99%